Pengembangan Model Pembelajaran Blended Learning dengan Dukungan AI untuk Mata Pelajaran Bahasa Indonesia di Era Digital - Alfanda, Wahyu; Nasir Azami, Muhammad; Hariyati (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2025)
This study aims to develop a blended learning model with AI support for Indonesian language subjects in elementary schools in the digital era. This research uses Research and Development (R&D) method with ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The participants involved 120 elementary school students from grades 4-6 and 12 Indonesian language teachers from 3 different schools in Pontianak. Data collection instruments include learning achievement tests, learning motivation questionnaires, and observation sheets. Data were collected through pre-test and post-test, questionnaires, interviews, and direct observation. Data analysis used descriptive statistical techniques and t-tests to measure effectiveness. The results showed that the blended learning model with AI support significantly improved students' Indonesian language learning outcomes by 28.5% compared to conventional learning methods. Students showed increased motivation (85.6%) and better digital literacy skills (78.9%). AI features such as adaptive learning, automatic assessment, and personalized feedback proved effective in supporting individualized learning. This model successfully integrates technology with face-to-face learning, creating an interactive and adaptive learning environment suitable for the digital era.